Cross-reactive and mono-reactive SARS-CoV-2 CD4+ T cells in prepandemic and COVID-19 convalescent individuals - Johansson, Alexandra M.; Malhotra, Uma; Kim, Yeseul G.; Gomez, Rebecca; Krist, Maxwell P.; Wald, Anna; Koelle, David M.; Kwok, William W. (PLoS pathogens, 2021)
Class II tetramer reagents for eleven common DR alleles and a DP allele prevalent in the world population were used to identify SARS-CoV-2 CD4+ T cell epitopes. A total of 112, 28 and 42 epitopes specific for Spike, Membrane and Nucleocapsid, respectively, with defined HLA-restriction were identified. Direct ex vivo staining of PBMC with tetramer reagents was used to define immunodominant and subdominant T cell epitopes and estimate the frequencies of these T cells in SARS-CoV-2 exposed and naïve individuals. Majority of SARS-CoV-2 epitopes identified have <67% amino acid sequence identity with endemic coronaviruses and are unlikely to elicit high avidity cross-reactive T cell responses. Four SARS-CoV-2 Spike reactive epitopes, including a DPB1*04:01 restricted epitope, with ≥67% amino acid sequence identity to endemic coronavirus were identified. SARS-CoV-2 T cell lines for three of these epitopes elicited cross-reactive T cell responses to endemic cold viruses. An endemic coronavirus Spike T cell line showed cross-reactivity to the fourth SARS-CoV-2 epitope. Three of the Spike cross-reactive epitopes were subdominant epitopes, while the DPB1*04:01 restricted epitope was a dominant epitope. Frequency analyses showed Spike cross-reactive T cells as detected by tetramers were present at relatively low frequency in unexposed people and only contributed a small proportion of the overall Spike-specific CD4+ T cells in COVID-19 convalescent individuals. In total, these results suggested a very limited number of SARS-CoV-2 T cells as detected by tetramers are capable of recognizing ccCoV with relative high avidity and vice versa. The potentially supportive role of these high avidity cross-reactive T cells in protective immunity against SARS-CoV-2 needs further studies.